Focal stenting of complex femoropopliteal lesions with the multi-LOC multiple stent delivery system: 12-month results of the multicenter LOCOMOTIVE study - Sigl, Martin (CardioVascular and interventional radiology, 2019)
Introduction: The purpose of this observational study is to report the 12-month clinical outcomes with the novel Multiple Stent Delivery System (MSDS) to treat complex femoropopliteal lesions. Previously, we reported the 6-month clinical outcomes of the all-comers LOCOMOTIVE study, which demonstrated the safety and efficacy of the MSDS with a favorable target lesion revascularization (TLR) rate of 5.3% and a 90.7% patency rate at 6 months in claudicants and critical limb ischemia patients. The 12-month outcomes of LOCOMOTIVE registry are presented in this report. ClinicalTrials.gov Identifier: NCT02531230. Methods: The LOCOMOTIVE study (Multi-LOC for flOw liMiting Outcomes after POBA and/or DCB Treatment in the infrainguinal position with the objecIVE to implant multiple stent segments) investigates the efficacy and safety of the MSDS approach in an all-comers population. Clinical follow-ups at 6 and 12 months are scheduled to assess TLR, ABI, and vessel patency based on sonographic imaging. Results: At 12 months, the primary unassisted patency was 85.7% and all-cause TLR rate was 9.3% in the overall cohort. Between baseline and 12 months, the target leg ABI increased from 0.62 ± 0.24 to 0.91 ± 0.38 (p < 0.001) and the mean Rutherford class improved from 3.5 to 1.9 (p < 0.001). Conclusions: Over a 12-month post-procedural period, MSDS for focal provisional stenting of complex femoropopliteal lesions demonstrated a promising primary patency and freedom from TLR after 12 months. In addition, significant improvements were observed in symptom classification and hemodynamics.
Gesehen am 09.04.2019
Published online: 25 October 2018